Rules, Communication, and Collusion: Narrative Evidence from the Sugar Institute Case - Genesove, David; Mullin, Wallace P (American Economic Review, 2001)
Detailed notes on weekly meetings of the sugar-refining cartel show how communication helps firms collude, and so highlight the deficiencies in the current formal theory of collusion. The Sugar Institute did not fix prices or output. Prices were increased by homogenizing business practices to make price cutting more transparent. Meetings were used to interpret and adapt the agreement, coordinate on jointly profitable actions, ensure unilateral actions were not misconstrued as cheating, and determine whether cheating had occurred. In contrast to established theories, cheating did occur, but sparked only limited retaliation, partly due to the contractual relations with selling agents. (JEL L13, L41)